2016
DOI: 10.1111/jgh.13207
|View full text |Cite
|
Sign up to set email alerts
|

Combined administration of propranolol + AG490 offers better effects on portal hypertensive rats with cirrhosis

Abstract: The combination of propranolol and AG490 caused a greater improvement of portal hypertension and might therefore offer a potentially promising therapy in the portal hypertension treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
(56 reference statements)
0
12
0
Order By: Relevance
“…There is increasing evidence that angiogenesis and neovascularization play an important role in the development of splenomegaly and hypersplenism. For example, the mammalian target of rapamycin (mTOR) and Janus kinase-2 (JAK2/STAT3) signaling pathways, which are known regulators of angiogenesis, have been implicated in the development of portal hypertension and splenomegaly, and inhibition of these signaling pathways has been shown to reduce splenomegaly ( Mejias et al., 2010 ; Wang et al., 2015 ; Chen et al., 2016 ; Wang et al., 2016 ). Furthermore, it has been reported that elevated levels of vascular endothelial growth factor (VEGF), a critical regulator of angiogenesis and neovascularization, are associated with splenomegaly in patients with chronic myeloid leukemia ( Liu et al., 2005 ) and polycythemia vera ( Murphy et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that angiogenesis and neovascularization play an important role in the development of splenomegaly and hypersplenism. For example, the mammalian target of rapamycin (mTOR) and Janus kinase-2 (JAK2/STAT3) signaling pathways, which are known regulators of angiogenesis, have been implicated in the development of portal hypertension and splenomegaly, and inhibition of these signaling pathways has been shown to reduce splenomegaly ( Mejias et al., 2010 ; Wang et al., 2015 ; Chen et al., 2016 ; Wang et al., 2016 ). Furthermore, it has been reported that elevated levels of vascular endothelial growth factor (VEGF), a critical regulator of angiogenesis and neovascularization, are associated with splenomegaly in patients with chronic myeloid leukemia ( Liu et al., 2005 ) and polycythemia vera ( Murphy et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is one of the cytokines involved in the development of angiogenesis[ 50 , 51 ]. Wang et al[ 52 ] found that AG490, a specific antagonist of JAK2, decreased the formation of new blood vessels in the liver by inhibiting the expression of JAK2/STAT3 signaling, which suppressed the activation of HSCs and reduced the expression of VEGF. JAK2/STAT3 signaling may stimulate vascular hyperplasia and decrease vascular tone by increasing the expression of VEGF, thus promoting the development of PHT.…”
Section: Jak2/stat3 Signalingmentioning
confidence: 99%
“…Endogenous angiogenesis and increased eNOS-derived nitric oxide levels in PHT have been considered important in the maintenance of PHT, and JAK2/STAT3 has been reported to promote eNOS protein expression[ 52 , 55 ].…”
Section: Jak2/stat3 Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the Janus kinase inhibitor AG490 significantly attenuated liver fibrosis in vivo and in vitro and decreased hepatic vascular resistance and portal pressure in cirrhotic rats [210–212]. In contrast to ACEi/ARB, add-on therapy with AG490 to propranolol resulted in an additive portal pressure-lowering effect in cirrhotic animals [213]. Similarly, the Rho-kinase inhibitor Y-27632 decreased fibrosis and lowered portal pressure without major systemic side effects [144,145] in animal studies.…”
Section: Renin–angiotensin–aldosterone Systemmentioning
confidence: 99%